(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Today, the problem of the formation of a free personality assumes that educational and educational work in educational institutions should be organized on the basis of modern innovative technologies. It is known that this process is not easy, but it is necessary to turn the current continuous education into a strictly scientifically based pedagogical system. Innovation pedagogical technology is such a field of knowledge, through which in the new millennium a fundamental turn occurs in the state’s policy in the field of Education, pedagogical activity is updated, a system of hurficrity, humanitarian feelings is formed in students and students. The stages of development of modern society are characterized by the strong influence of innovation-computer technology on it. One of the integral and important parts of scientific and pedagogical activity is the perfect organization of the system of effective use of innovation-computer technologies in the educational process. A number of works are currently underway on the line. These works are reflected in the application of new methods and innovation technologies in the educational process. Because, the use of interactive e-learning courses on the basis of computer and multimedia technologies in the educational process is considered as the main tool that allows you to increase the effectiveness of Education. Currently, the number of young people who know how to use computers and Multimedia Tools has increased significantly.